Assisting in long term care : Mary Jo Mirlenbrink Gerlach, Barbara R. Hegner - Gerlach, Mary Jo Mirlenbrink; Hegner, Barbara R. (Delmar health care, 2014)
Delivers required content to prepare students for the certification exam, along with features that develop critical skills for working in long-term care and sub-acute hospital settings. This book includes review questions and self-tests, icons to point out key material, and robust package of interactive, supplemental learning and teaching tools